Study on the characteristics of micro, small and medium enterprises (case study of Bu Tun grocery store): Inggris - Iis Azmiyati; Yuni Prihadi Utomo (Jurnal Ekonomi, 2024)
One type of business popular with the community, especially the lower middle class, is the grocery store. The grocery store itself is a store that is a provider of basic daily necessities. Bu Tun grocery store is a small industry that has been in existence since 2000 and has been a provider of various types of basic needs for the community. This store is located in Kebonan Village, Karanggede District. The purpose of this research is the identification and analysis of business, economic and social aspects. The data analysis method used is descriptive qualitative analysis. From the results of data analysis, the author found that with regard to the results of analysis on the entrepreneurial aspect c, there are 3 main characters, namely the characters of persistence, perseverance and religiosity. Then from the analysis of the results on the economic aspect, which includes firstly capital for the basic food business, Bu Tun uses personal capital in setting up this business, bookkeeping, in terms of bookkeeping this shop has not yet used opening, selecting suppliers, in terms of selecting suppliers it was found that this shop has 3 criteria in selecting The first main supplier is price, delivery and quality. From the results of the analysis on social aspects, it was found that the current market conditions are increasingly calm due to the development of the modern market. and the absence of the government's role in promoting the Karanggede market.